Preparation, microstructure and electromagnetic property of SnO2 powder by co-precipitation method at different calcined temperature. (July 2015) - Su, X.; Luo, F.; Zhao, K.; Jia, Y.; Wang, J.; Xu, J.; He, X.; Qu, Y.; Fu, C.; Liu, S.; Ma, L.
Abstract : SnO2 powders have been prepared by co-precipitation method at different calcined temperature using tin chloride (SnCl4 ·5H2 O) as the raw material and ammonium hydroxide (NH3 ·H2 O) as the precipitator respectively. The microstructure of the prepared powders has been characterised by X-ray diffraction and scanning electron microscope (SEM) respectively. Results show that the grain size and lattice constant of prepared powders increased with increasing calcined temperature. The electromagnetic property of prepared powders in the frequency range of 8·2–12·4 GHz has been determined. The real part ϵ ′ and imaginary part ϵ ″ of permittivity of prepared powders decreased with increasing calcined temperature. There was little change of real part μ′ and imaginary part μ″ of permeability of prepared powders.